Phenotypic plasticity of invasive Spartina densiflora (Poaceae) along a broad latitudinal gradient on the Pacific Coast of North America1. Issue 3 (1st March 2014) - Castillo, Jesús M.; Grewell, Brenda J.; Pickart, Andrea; Bortolus, Alejandro; Peña, Carlos; Figueroa, Enrique; Sytsma, Mark
Abstract : Premise of the study: Phenotypic acclimation of individual plants and genetic differentiation by natural selection within invasive populations are two potential mechanisms that may confer fitness advantages and allow plants to cope with environmental variation. The invasion of Spartina densiflora across a wide latitudinal gradient from California (USA) to British Columbia (Canada) provides a natural model system to study the potential mechanisms underlying the response of invasive populations to substantial variation in climate and other environmental variables. Methods: We examined morphological and physiological leaf traits of Spartina densiflora plants in populations from invaded estuarine sites across broad latitudinal and climate gradients along the Pacific west coast of North America and in favorable conditions in a common garden experiment. Key results: Our results show that key foliar traits varied widely among populations. Most foliar traits measured in the field were lower than would be expected under ideal growing conditions. Photosynthetic pigment concentrations at higher latitudes were lower than those observed at lower latitudes. Greater leaf rolling, reduced leaf lengths, and lower chlorophyll and higher carbon concentrations were observed with anoxic sediments. Lower chlorophyll to carotenoids ratios and reduced nitrogen concentrations were correlated with sediment salinity. Our results suggest that the variations of foliar traits recorded in the field are a plastic phenotypic response that was not sustained under common garden conditions. Conclusions: Spartina densiflora shows wide differences in its foliar traits in response to environmental heterogeneity in salt marshes, which appears to be the result of phenotypic plasticity rather than genetic differentiation.